Long‐term community noise exposure in relation to dementia, cognition, and cognitive decline in older adults. Issue 3 (20th October 2020) - Weuve, Jennifer; D'Souza, Jennifer; Beck, Todd; Evans, Denis A.; Kaufman, Joel D.; Rajan, Kumar. B.; de Leon, Carlos F. Mendes; Adar, Sara D.
Abstract: Introduction: Exposure to noise might influence risk of Alzheimer's disease (AD) dementia. Methods: Participants of the Chicago Health and Aging Project (≥65 years) underwent triennial cognitive assessments. For the 5 years preceding each assessment, we estimated 5227 participants' residential level of noise from the community using a spatial prediction model, and estimated associations of noise level with prevalent mild cognitive impairment (MCI) and AD, cognitive performance, and rate of cognitive decline. Results: Among these participants, an increment of 10 A‐weighted decibels (dBA) in noise corresponded to 36% and 29% higher odds of prevalent MCI (odds ratio [OR] = 1.36; 95% confidence interval [CI], 1.15 to 1.62) and AD (OR = 1.29, 95% CI, 1.08 to 1.55). Noise level was associated with worse global cognitive performance, principally in perceptual speed (–0.09 standard deviation per 10 dBA, 95% CI: –0.16 to –0.03), but not consistently associated with cognitive decline. Discussion: These results join emerging evidence suggesting that noise may influence late‐life cognition and risk of dementia.